MicroRNA-935 Directly Targets FZD6 to Inhibit the Proliferation of Human Glioblastoma and Correlate to Glioma Malignancy and Prognosis - Zhang, Dainan; Ma, Shunchang; Zhang, Chuanbao; Li, Peiliang; Mao, Beibei; Guan, Xiudong; Zhou, Wenjianlong; Peng, Jiayi; Wang, Xi; Li, Shaomin; Jia, Wang (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) are involved in human glioblastoma (GB). MiR-935 has been reported to have both tumor-inhibiting and tumorigenesis effects, but its role in GB remains unclear. Because of the high mortality and morbidity associated with the malignancy of GB, a deeper understanding of the molecular crosstalk that occurs in GB is needed to identify new potential targets for treatment. At present, the mechanism of GB at the molecular level is not fully understood. With the aid of bioinformatic analysis, miR-935 was significantly downregulated in GB, and it presented a poorer outcome. In the glioma cell line and in the nude mice model, the miR-935 inhibited cell proliferation by modulating cell circles in vitro and in vivo. Then, the target genes of miR-935 were analyzed by using the online database, and the direct binding was tested with a luciferase analysis. FZD6 was found to be the direct target of miR-935. The effect of miR-935 was recovered by the overexpression of FZD6 in vitro. In addition, the negative correlation of miR-935 and the expression of FZD6 were confirmed in our clinical samples, and the expression of FZD6 has a strong correlation with tumor malignancy and prognosis. This study showed that miR-935 directly inhibited the expression of FZD6 and inhibited the cell proliferation, thereby suppressing the development of GB, suggesting that miR-935 is a cancer suppressor miRNA and may become a prognostic biomarker or a promising potential therapeutic target for human GBs.